IT investment management and information technology portfolio management (ITPM): Brazilian case studies. Issue 6 (23rd August 2014) - Dolci, Pietro Cunha; Maçada, Antonio Carlos Gastaud; Grant, Gerald G.
Abstract : Purpose: The objective of this research is to analyze some Brazilian companies' use of the ITPM technique as an aid to their IT investments management Design/methodology/approach: It was carried out in five case studies in different Brazilian companies from several economic sectors which were using ITPM or were in the initial implementation phase. Eight interviews were conducted. The persons interviewed were high-level executives working in the IT department in the studied companies. Findings: Different levels of ITPM use was found with respect to IT investment management (planning, control and evaluation). It was observed, in the analyzed cases, that ITPM is used most frequently in IT investment planning, which is the process most discussed and used in analyzed companies. The ITPM technique is used more frequently in Company 2 than in the other cases because the organization of the IT area in the company is structured according to ITPM dimensions Research limitations/implications: The ITPM technique has received little attention in IT research and research in this area identifying the use and applicability of ITPM in companies is still very limited in the information systems literature. Originality/value: The paper presents IT investment management in different Brazilian companies and how ITPM was used to help companies in this process compose by planning, control and evaluation.